'Como fa la foja': Versions of Female Authority in the Huon d'Auvergne Manuscript Tradition. (February 2015) - McCormick, Stephen P.
<x content-type="archive" xml:space="preserve">Abstract</x> This essay investigates the variant representations of female authority and rebellion in the Franco-Italian Huon d'Auvergne romance-epic manuscript tradition. Taking textual variance as a productive, not obstructive, locus of analysis, this inquiry focuses on one of the more textually unstable episodes of the Huon epic, the resistance of Huon's wife Ynide to king Carlo Martello's consuming passion. Sidestepping concerns about the earliest or best manuscript version of Ynide's defence episode, this essay examines the female protagonist's mutable textual situation within the context of changing ideals of womanly virtue in the fourteenth century.